Seasonal patterns of melatonin alter aggressive phenotypes of female Siberian hamsters. (18th August 2020) - Rendon, Nikki M.; Petersen, Christopher L.; Munley, Kathleen M.; Amez, Andrea C.; Boyes, Daniel L.; Kingsbury, Marcy A.; Demas, Gregory E.
Abstract: Many animal species exhibit year‐round aggression, a behaviour that allows individuals to compete for limited resources in their environment (eg, food and mates). Interestingly, this high degree of territoriality persists during the non‐breeding season, despite low levels of circulating gonadal steroids (ie, testosterone [T] and oestradiol [E2 ]). Our previous work suggests that the pineal hormone melatonin mediates a 'seasonal switch' from gonadal to adrenal regulation of aggression in Siberian hamsters ( Phodopus sungorus ); solitary, seasonally breeding mammals that display increased aggression during the short, 'winter‐like' days (SDs) of the non‐breeding season. To test the hypothesis that melatonin elevates non‐breeding aggression by increasing circulating and neural steroid metabolism, we housed female hamsters in long days (LDs) or SDs, administered them timed or mis‐timed melatonin injections (mimic or do not mimic a SD‐like signal, respectively), and measured aggression, circulating hormone profiles and aromatase (ARO) immunoreactivity in brain regions associated with aggressive or reproductive behaviours (paraventricular hypothalamic nucleus [PVN], periaqueductal gray [PAG] and ventral tegmental area [VTA]). Females that were responsive to SD photoperiods (SD‐R) and LD females given timed melatonin injections (Mel‐T) exhibited gonadal regression and reduced circulating E2, but increased aggression and circulating dehydroepiandrosterone (DHEA). Furthermore, aggressive challenges differentially altered circulating hormone profiles across seasonal phenotypes; reproductively inactive females (ie, SD‐R and Mel‐T females) reduced circulating DHEA and T, but increased E2 after an aggressive interaction, whereas reproductively active females (ie, LD females, SD non‐responder females and LD females given mis‐timed melatonin injections) solely increased circulating E2 . Although no differences in neural ARO abundance were observed, LD and SD‐R females showed distinct associations between ARO cell density and aggressive behaviour in the PVN, PAG and VTA. Taken together, these results suggest that melatonin increases non‐breeding aggression by elevating circulating steroid metabolism after an aggressive encounter and by regulating behaviourally relevant neural circuits in a region‐specific manner. Abstract : In the present study, we tested the hypothesis that melatonin elevates non‐breeding aggression in Siberian hamsters by increasing circulating and neural steroid metabolism. We found that female hamsters given a short day‐like melatonin signal, either via timed melatonin injections (Mel‐T) or exposure to short‐day photoperiods (SD‐R), reduced circulating dehydroepiandrosterone and testosterone levels, but increased circulating oestradiol levels after an aggressive interaction. Furthermore, SD‐R and Mel‐T females showed similar associations between aggressive behaviour and neural aromatase abundance in the paraventricular hypothalamic nucleus and periaqueductal gray, suggesting a role for melatonin in mediating seasonal changes in steroidogenesis and aggressive behaviour.